Pengaruh Konsumsi Jus Kelor (Moringa Oleifera) terhadap Peningkatan Produksi Asi pada Ibu Menyusui di Desa Mantobua, Sulawesi Tenggara - Sarumi, Rasniah; Sari, Elna (Universitas Batanghari Jambi, 2022)
Mother's nutritional status greatly influences breast milk production so that the food consumed by the mother must increase breast milk production, namely Moringa (Moringa Olifeira). The purpose of this study was to determine the effect of consuming Moringa Oleifera juice on increasing milk production in breastfeeding mothers in Mantobua Village, Southeast Sulawesi. The research method uses a quantitative type with a quasi-experimental design (pre-experiment). The approach used is the one group pre-post design, which is one of the pre-experimental methods where there is no comparison group (control) but the first observation (pre-test) has been carried out which examines the changes that occur after the treatment. The population in this study were 38 breastfeeding mothers in Mantobua Village who were registered at the Waara Health Center in January 2022. The number of samples is 38 people. The sampling technique uses a saturated sampling technique, namely the entire population is used as a sample. Data were analyzed using the Wilcoxon test. The results of this study indicate that the age of the respondents is dominated by 10 respondents aged 31-35 years (26.3%), the majority of respondents are housewives with 25 persons (65.8%) and there is influence of consumption of Moringa juice (Moringa Olifeira ) on increasing breast milk production in Mantobua Village. The conclusion that Moringa juice can increase milk production.